2008
DOI: 10.1159/000136654
|View full text |Cite
|
Sign up to set email alerts
|

Belgian Observational Drug Utilization Study of Pimecrolimus Cream 1% in Routine Daily Practice in Atopic Dermatitis

Abstract: Background: For reimbursement purposes of pimecrolimus cream 1%, the Belgian authorities asked to document its consumption, its topical corticosteroid-sparing effect and quality of life within the routine clinical practice. Objectives: We aimed to address the 3 queries of the Belgian authorities. Methods: An open-label, observational, multicentre, 1-year study under drug prescription was performed. Results: A total of 416 consecutive patients were enrolled in 49 centres. The mean annual amount of prescribed pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…During this study, topical corticosteroids were not used in 36.0% of the patients with previous topical corticosteroid use and 60.7% of patients without previous use. [77,78] In two 6-week studies, [81] a significant difference in PIQoL-AD score was reported between the topical pimecrolimus and vehicle groups (table IV). [79] Topical pimecrolimus was more effective than vehicle in improving the HR-QOL of parents whose children had atopic dermatitis in short-term, continuous-use studies [80,81] and longer term, intermittent-use studies.…”
Section: Health-related Quality Of Lifementioning
confidence: 96%
See 3 more Smart Citations
“…During this study, topical corticosteroids were not used in 36.0% of the patients with previous topical corticosteroid use and 60.7% of patients without previous use. [77,78] In two 6-week studies, [81] a significant difference in PIQoL-AD score was reported between the topical pimecrolimus and vehicle groups (table IV). [79] Topical pimecrolimus was more effective than vehicle in improving the HR-QOL of parents whose children had atopic dermatitis in short-term, continuous-use studies [80,81] and longer term, intermittent-use studies.…”
Section: Health-related Quality Of Lifementioning
confidence: 96%
“…[77][78][79] After 1 year of intermittent treatment, the mean CDLQI score was significantly lower in the topical pimecrolimus than in the vehicle group (table IV). [78] In a postmarketing study, [79] topical pimecrolimus for 4-6 weeks (1.73% of patients received topical corticosteroids) was associated with improvement in HR-QOL in 1438 pediatric patients (aged ‡2 to <17 years) with atopic dermatitis (baseline disease severity not stated) [CDLQI at study end was 4.7; baseline CDLQI was 12.2]. During this study, topical corticosteroids were not used in 36.0% of the patients with previous topical corticosteroid use and 60.7% of patients without previous use.…”
Section: Health-related Quality Of Lifementioning
confidence: 97%
See 2 more Smart Citations
“…The use of topical pimecrolimus was associated with improvements in the HR-QOL of pediatric patients with atopic dermatitis in a large postmarketing study. [26] The HR-QOL of parents whose children had atopic dermatitis was associated with greater improvements in the topical pimecrolimus group compared with the vehicle group, in short-term, continuoususe [27,28] and longer term, intermittent-use [25,29] trials.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%